Awareness of cosmetic dermatology procedures among health workers in a Tertiary Care Hospital - Deeptara P Thapa (Wolters Kluwer Medknow Publications, 2019)
Introduction: Cosmetic dermatology is a branch of dermatology which deals with the enhancement of beauty. There is a rise in cosmetic dermatological procedures throughout the world, but its awareness is limited not only in the general population but also among the health workers. Materials and Methods: We conducted a cross-sectional questionnaire-based study to know the knowledge and awareness of cosmetic dermatological procedures among health workers in a hospital setting. Results: There were a total of 155 respondents. The maximum number of respondents belonged to age group of 20-30 years (65.2%). Female respondents were 66% and males were 34%. Of the total respondents, 39% were medical students, 31% doctors, 23% nurses, 6% OPD assistants, and 1% ward maids. Hinduism was practiced by 91% of the respondents. About 84.5% of subjects were aware of cosmetic dermatological procedures. Regarding the source of information, 34.2% implicated textbooks. According to 53.5% participants, cosmetic dermatological procedures are done by a dermatologist. Around 59.4% responded that they were aware of many procedures such as botox injections, laser hair removal, hair transplant, and chemical peeling; 51% were aware of risks associated with procedures, such as allergy, burns, and pigmentation; 44.5% rated the facility as good; 31% believed that outcome of the procedures is different in Nepal as compared to a foreign countries. About 23.9% thought public disposition will change if they underwent the procedures. Around 11.6% thought this shall negatively affect them; however, 53.5% believed it would be socially acceptable. About 78.1% thought that these procedures are done only in cities with 62.6% believing it is commonly done by high-class economic status people. About 73.5% respondents believed that this was adopted by literate people; 7.1% were concerned about taboos against cosmetic dermatosurgical procedures; 84.5% agreed that there should be awareness program on these procedures. Conclusion: We found lack of awareness, knowledge, attitudes, and disposition about cosmetic dermatosurgical procedures among health workers. Further community-based population studies and awareness programmes should be carried out regarding this aspect.